Editorial de la revista número 4 del año 2015 - Alfie, José (Revista del Hospital Italiano de Buenos Aires, 2015)
This issue of the Journal updates two neurological entities. Herpes simplex virus 1 (HSV1) encephalitis is the most common cause of fatal viral infection of the central nervous system, and the only one with a specific treatment. Clinical suspicion in a patient presenting with fever and confusional syndrome, focal motor deficit, aphasia, ataxia, or generalized tonic-clonic seizure allows for early initiation of acyclovir.The classic mechanism of ischemic stroke (IS) is the thrombotic or embolic occlusion of a cerebral artery. Hemodynamic stroke occurs when collateral circulation fails to compensate for the blood flow to a territory distal to an occluded or critically stenosed cerebral artery, in the context of absolute or relative hypotension.The Original Article analyzes the feasibility of initiatives to promote a healthy work environment in a hospital service.In Internal Medicine in Imaging, the value of magnetic resonance imaging in the diagnosis of infiltrative cardiomyopathies such as amyloidosis is illustrated.In the “Hospital Italiano in Medline” section, the authors comment on their article Quaternary Prevention in Psychogeriatrics, which discusses the undesired consequences of medicalizing situations that do not constitute a disease but rather emotional distress in response to grief or aging.In the Humanities section, the curative potential of the shaman in hunter-gatherer societies is analyzed.In the Art and Human Nature section, the theme of hope is addressed through the play Waiting for Godot.